Pola Perubahan Spasial Daerah Pinggiran Kota (Urban Fringe) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Ekonomi,UGM, 1997)
Urban development pressure have not resulted in the spatial transformation of urban center but also urban fringe area. The spatial transformation of urban fringe area can be seen in the growth of urban area which is represented by the escalation of the conversion of agricultural land into non-agricultural land that is dominated by housing area.This research is focused in analyzing spatial transformation pattern that is occured in urban fringe area. The analysis was conducted by graphical and visual analyses of macro level and making comparisons of villages in relation to the local social-structure.